2018
DOI: 10.1177/0265407518816883
|View full text |Cite
|
Sign up to set email alerts
|

As the states turned: Implications of the changing legal context of same-sex marriage on well-being

Abstract: Using a minority stress framework, we examined changes in personal well-being among individuals in same-sex relationships during the transition to federal marriage recognition. Longitudinal panel data from 279 individuals were collected once before and at three time points after the U.S. Supreme Court decision in the Obergefell vs. Hodges case that resulted in federal recognition of same-sex marriage. Prior to the ruling, levels of internalized homonegativity, isolation, and vicarious trauma were positively as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 58 publications
1
25
0
1
Order By: Relevance
“…absence of same-sex marriage and/or same-sex parenting laws, and of hate crime laws; and cultural norms and institutional political initiatives that constrain the opportunities and access to resources by GSM individuals) (e.g. Ogolsky et al, 2019); (2) at an interpersonal level (e.g. family rejection, school bullying, abuse, and microaggressions such as use of derogatory terms and negative reactions to public display of affection) (Balsam et al, 2005); and (3) at an individual level (i.e.…”
Section: Gsms and Mental Healthmentioning
confidence: 99%
“…absence of same-sex marriage and/or same-sex parenting laws, and of hate crime laws; and cultural norms and institutional political initiatives that constrain the opportunities and access to resources by GSM individuals) (e.g. Ogolsky et al, 2019); (2) at an interpersonal level (e.g. family rejection, school bullying, abuse, and microaggressions such as use of derogatory terms and negative reactions to public display of affection) (Balsam et al, 2005); and (3) at an individual level (i.e.…”
Section: Gsms and Mental Healthmentioning
confidence: 99%
“…With regard to minority stress in particular, one study included in our review found that parental internalized homonegativity moderated the association between a state's legal climate and changes in depression and anxiety during the 1st year of parenthood (Goldberg and Smith, 2011 ). On the individual level, minority stress has also been found to moderate the impact of sexual orientation laws (e.g., Bauermeister, 2014 ; Pachankis et al, 2014 ; Hylton et al, 2017 ; Ogolsky et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Even before 2015, many same-sex couples who were legally married in another state or country considered themselves to be married, even if the state in which they lived did not recognize their marriage (DeMaio, Bates, & O'Connell, 2013). Policy changes, such as national legalization of marriage for same-sex couples, may reduce sexual minority stigma and experiences of minority stress (Herek, 2006;Ogolsky, Monk, Rice, & Oswald, 2019a;Tatum, 2017). Studies about the potential impacts of legal marriage are needed to better understand how being married may or may not reduce sexual-orientation-related disparities in substance use outcomes.…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%